Association of age at menarche with valvular heart disease: An analysis based on electronic health record (CREAT2109) - Zhiyu Sun; Zhiyu Sun; Zhiyu Sun; Yongjie Zhu; Xiaoyan Sun; Zhexun Lian; Zhexun Lian; Mengqi Guo; Xiaohong Lu; Ting Song; Luxin Feng; Yi Zhang; et al. (Frontiers in Cardiovascular Medicine, 2023)
BackgroundThe association between age at menarche and coronary heart disease has been reported, but the association between age at menarche and valvular heart disease (VHD) has not been described. We aimed to examine the association between age at menarche and VHD.MethodsBy collecting data from four medical centers of the Affiliated Hospital of Qingdao University (QUAH) from January 1, 2016, to December 31, 2020, we sampled 105,707 inpatients. The main outcome of this study was newly diagnosed VHD, which was diagnosed based on ICD-10 coding, and the exposure factor was age at menarche, which was accessed through the electronic health records. We used logistic regression model to investigate the association between age at menarche and VHD.ResultsIn this sample (mean age 55.31 ± 13.63 years), the mean age at menarche was 15. Compared with women with age at menarche 14–15 years, the odds ratio of VHD in women with age at menarche ≤13, 16–17, and ≥18 years was 0.68 (95% CI 0.57–0.81), 1.22 (95% CI 1.08–1.38), and 1.31 (95% CI 1.13–1.52), respectively (P for all < 0.001). By restricting cubic splines, we found that later menarche was associated with increased odds of VHD (P < 0.001). Furthermore, in subgroup analysis of different etiologies, the similar trend persisted for non-rheumatic VHD.ConclusionsIn this large inpatient sample, later menarche was associated with higher risk of VHD.